Premature graying of hair: Risk factors, co‐morbid conditions, pharmacotherapy and reversal—A systematic review and meta‐analysis. Issue 6 (28th July 2020) - Mahendiratta, Saniya; Sarma, Phulen; Kaur, Hardeep; Kaur, Sukhmandeep; Kaur, Harpinder; Bansal, Seema; Prasad, Davinder; Prajapat, Manisha; Upadhay, Sujata; Kumar, Subodh; Kumar, Harish; Singh, Rahul; et al.
Abstract: Premature graying of hair (PGH) being a very common entity for which pharmacotherapy and reversibility are not properly addressed. Therefore, this systematic review was conducted to address these issues. For this relevant study were selected from various databases including PubMed, EMBASE, OVID, Web of science, Scopus, and Google Scholar till January 20, 2019. Studies which reported risk factors, co‐morbid conditions associated with PGH, its pharmacotherapy and reversal were included in the study. Although many risk factors are reported in literature, smoking, vitamin deficiency (B12, folic acid, and B7), mineral deficiency (low serum calcium and serum ferritin) are found to be associated with PGH. Other important risk factors are family history of PGH, obesity, high B.P, lack of exercise, drugs, genetic syndromes, dyslipidemia, thyroid disorders, hyperuricemia, and alteration in liver function. PGH is found to be an important marker of CAD, more so in case of smoker. Among different pharmacotherapeutic management options, low grade recommendation (2A) is given to calcium pantothenate, PABA, calcium pantothenate + PABA combination. Anu‐tailam is the only herbal agent evaluated in clinical research settings. Finally, treating the accompanying pathologies led to the reversal of the disease in many cases.